Suspicious oral lesions. Issue 7 (July 2021) - Collins, Timothy
Oral lesions typically present as swellings/lumps or mucosal lesions. Mucosal lesions can be red, white, red-and-white or pigmented. Lesions are typically incidental findings in routine dental examinations of asymptomatic patients. Symptoms (typically soreness) prompt patients to seek advice from GPs as well as dentists. Oral ulceration is a common reason for presentation and may indicate a suspicion of underlying pathology. It is common for mucosal lesions to warrant referral, but it is useful to identify benign pathology to inform the urgency of referral. The study of suspicious oral pathology, in addition to benign pathology mimicking suspicious aetiology, forms a significant component of the dental undergraduate curriculum. This is a large topic and full familiarity will require reading beyond the scope of this article.